Developing rubrics for designing language computer-enhanced lessons - De Guzman, Carmela F. (2006)
This study attempted to develop valid and reliable rubrics for assessing computer-enhanced lessons. A survey of Language teachers drew out their perceptions, insights, and other opinions as to what is important in computer-enhanced lessons. From these responses, draft rubrics were prepared to monitor different levels of performance in instructional design ang pedagogical soundness, and content and multimedia elements. After pilot testing and some refinements, the rubrics were used by grade school Language teachers to rate computer-enhanced lessons in Grade 7 grammar. Based on their opinion from the degree of concordance during content validation and during the inter-rater test, the rubrics developed are valid and reliable assessment instruments